The Concept of Digital Capitalism. Issue 3 (18th April 2018) - Pace, Jonathan
Abstract: In this article, I develop a dialectical, historical account of digital capitalism that moves beyond nominalist and structuralist approaches. I proceed in three parts. First, I provide an overview of the topical literature, focusing on the exemplary work of D. Schiller (1999) and C. Fuchs (2013). Second, I define capitalism in its dual capacity as an abstract system with core features and a nominal series of historical developments. Third, I reformulate the concept of digital capitalism and sketch the relation between digital media and capitalism as a point of departure for future research. I conclude with a discussion of structuralism and nominalism in contemporary media theory.